" أثر الحوافز على تنمية السلوك الإبداعي للعاملين دراسة ميدانية ببلدية سيدي عمران " - أنتصار فرحات; رميصاء درداش; رزيقة رحال; محمود أوبيري (جامعة الوادي university of eloued, 2024)
"هناك مجالات متعددة ومتنوعة يمكن استكشاف وتحويلها إلى فرص إبداعية كبيرة ،مما يعزز قدرات وإمكانات الفرد .فالحوافز تعد أحد الركائز الأساسية التي تساعد على تنمية السلوك الإبداعي لدى الموظفين في منظمات الأعمال إذ توفر البيئة المناسبة للإبداع ،والذي بدوره يسهم في تقدم المؤسسة وازدهارها . هده الدراسة تهدف إلى تطبيق الحوافز المادية والمعنوية ودراسة مدى تأثيرها على تنمية السلوك الإبداعي للموظفين في بلدية سيدي عمران، تم توزيع استبيان على عينة عشوائية منتظمة من 40 موظف وتم تحليله باستخدام البرنامج الإحصائية SPSS وأهم ما توصلت له الدراسة أنه هناك تأثير متوسط إلى كبير من الحوافز المطبقة على السلوك الإبداعي للعاملين داخل بلدية سيدي عمران، كذلك وجود ثقافة كبير عند العاملين بثقافة التحفيز والسلوك الإبداعي. " "There are multiple and diverse fields that can be explored and transformed into great creative opportunities, which enhance the capabilities and potential of the individual. Incentives are one of the basic pillars that help develop creative behavior among employees in business organizations, as they provide the appropriate environment for creativity, which in turn contributes to the organization’s progress and prosperity. This study aims to apply material and moral incentives and study the extent of their impact on developing the creative behavior of employees in the Sidi Amran Municipal Corporation. A questionnaire was distributed to a regular random sample and the most important findings of this study. ASPSS of 40 employees and was analyzed using the statistical program: There is a moderate to large impact of the incentives applied on the creative behavior of employees within the municipality of Sidi Amrane, as well as the presence of great awareness among employees of the culture of motivation and creative behavior . "
Keywords: حوافز، حوافز مادية، حوافز معنوية، سلوك الإبداعي. incentives; material incentives; moral incentives; creative behavior